Peranan Sekretaris dalam Membantu Kelancaran Administrasi BAPPEDA Provinsi Aceh - Yusnawati; Tri Murni (Jurnal Ekonomi Manajemen dan Sekretari, 2021)
BAPPEDA (Regional Development Planning Agency) Aceh Province is the government agency responsible for planning, coordinating and overseeing the implementation of development programs in the region. In carrying out its duties, BAPPEDA needs assistance from a secretary who can help expedite administration. This article examines the important role played by a secretary in assisting the smooth administration of BAPPEDA Aceh Province, including the tasks that a secretary must carry out, the skills and abilities needed, and the challenges that may be faced while carrying out their duties. The research was conducted through interviews with several BAPPEDA secretaries and data analysis to present a practical view of the roles and responsibilities of a secretary in ensuring smooth administration at BAPPEDA Aceh Province.